Nondestructive tomographic imaging of rust with rapid thz time-domain spectroscopy - Kim, Hwan Sik; Baik, Seung Yeob; Lee, Joong Wook; Kim, Jangsun; Ahn, Yeong Hwan (Applied Sciences (Switzerland), 2021)
In this study, we developed a rapid nondestructive tool for testing rust spread in a metal covered by a paint layer by using a THz time-domain spectroscopy system at a speed of 100 Hz/pixel. Time-of-flight imaging helps identify rust formation by exclusively obtaining the reflection from the steel below the paint surface. The use of frequency-selective imaging allows us to manipulate the contrast in rust imaging. Higher contrast is generally obtained when monitoring using the higher frequency component. In addition, we monitored the spread of rust in a steel plate under the influence of two different chemical solutions: NaCl and acid. We found that in the early stages, the decrease in THz reflection was governed by the high-frequency components due to the formation of lepidocrocite, whereas the low-frequency component develops as the proportion of hematite increases with time.
Keywords: Nondestructive testing; Rust; Terahertz imaging